Mobility in a Stationary Place: Labor and Ethical Conditions in the Philippine BPO Industry in Glen Diaz's The Quiet Ones - Honeylet Alerta (POETIKA, 2023)
All over the world, Business Processing Outsource (BPO) companies have been set up to provide services that would enable utmost efficiency to business-related work operations.  BPOs have been fertile ground for dreams of mobility and freedom for their employees. Illustrative is the 2017 Philippine novel in English, The Quiet Ones by Glenn Diaz, which frames the lives of call center agents who steal from the multimillion-dollar American-based BPO company and remain remorseless even after they have been caught for the crime. The novel narrates how the contemporary lives of Filipinos are drastically shaped by their experience of working as call center agents, highlighting their various unethical ‘traversals’ behind the stationary façade of the industry in order to escape from their sense of disempowerment. This paper would like to show how the novel’s depiction of the BPO industry's shrinking physical and imagined spaces, protocols in customer service, and its bureaucracy are symptomatic of the call center agents’ obsession, psyche, and modes of surviving the system. To do that, careful attention will be given to the portrayal of the experience of the physical, representational, and mobile practices in the BPO industry. While the BPO industry plays an essential role in the economic progress of the Philippines, it has also affected the material and mobile conditions of Filipino call center agents, as they follow a business model of efficacy aligned with the larger scheme of global capitalism. Such efficacy is underpinned by a kind of ‘modern’ ethics specific to the BPO call centers concretizing the betrayal of globalization's promise of proper mobility and freedom as embodied by the infrastructure of the call center offices shaping the superstructural official practice and ‘call center culture.’